The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1413-81232017229.12712017
|View full text |Cite
|
Sign up to set email alerts
|

Violência de gênero: comparação da mortalidade por agressão em mulheres com e sem notificação prévia de violência

Abstract: Violence against women is an important public health problem in (2011 -2015), and SIM, the Mortality Information System (women dying as a result of aggression) (2011 -2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
64

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(126 citation statements)
references
References 19 publications
0
29
1
64
Order By: Relevance
“…Gender violence is an ancient phenomenon, produced from social, cultural, political and historical constructions, which can be inserted into the daily life of women from childhood, adulthood and old age 13 . In Brazil, despite advances in public policies and punitive laws, exorbitant levels of such violence remain 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Gender violence is an ancient phenomenon, produced from social, cultural, political and historical constructions, which can be inserted into the daily life of women from childhood, adulthood and old age 13 . In Brazil, despite advances in public policies and punitive laws, exorbitant levels of such violence remain 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth mentioning the increase in the proportion of deaths occurring on public roads in all Brazilian regions (11) , it is believed that many partners or former partners, because they know the routine of the victims, can perpetrate the aggression in the exit of home, work or school, and thus many women may be terminating abusive relationships, using the prerogatives of the Maria da Penha Act. However, they have not received the necessary protection from the State to prevent deaths (8,(10)(11)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a legal apparatus to repress this type of violence, there is a gap between legislation and practice, from the invisibility that crosses violence against women to the difficulty of articulating a resolute care network to combat this violence (1,8) . In this direction, a study comparing homicide mortality in women with and without prior notification of violence showed that 15.0% of women who died due to feminicide in Brazil in the period from 2011 to 2015 had reported domestic violence, indicating limitations and weaknesses of the care and attention network for women (9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…In general, they perform specific and normative actions for cases whose complexity requires the re-signification of habits and culture and, therefore, require continuous changes in the search for a new social order, that of gender equality. Thus, professionals working in the UBS/ESF and CRAS must break with the one-off medical care focused on PHC, assistance in basic social protection 39,40 .…”
Section: The Types Of Violencementioning
confidence: 99%
“…Notifying violence without articulated and integrated actions does not diminish women's vulnerability. A study with data from SINAN and SIM for Brazil from 2011 to 2015 shows that the risk of women notified due to violence dying from abuse is higher than that of the female population in general 40 .…”
Section: The Types Of Violencementioning
confidence: 99%